COUNTER HEGEMONY SPECTACLE STEREOTIP WARIA DALAM INDUSTRI BUDAYA PADA FILM DOKUMENTER NGUDAL PIWULANG WANDU - Kukuh Yudha Karnanta (Universitas 17 Agustus 1945 Surabaya, 2016)
Abstract. This article discusses two main issues: (1) the effort of counter hegemoni presented in Ngudal Piwulang Wandu documentary film featuring the figure of the Nyi Suci alias Soleh as the mastermind transvestite; (2) the representation of transvestites as an object of entertainment in the context of the cultural industry in Indonesia which produced a certain negative stigma streotipe and on transgender community. The study uses the theory of spectacle and counter hegemony cinematic to explain the significance of the appearance of the film related to the presence NPW transvestites in Indonesia.Kata-kata kunci: Waria, Wayang Kulit, dan Kontrahegemoni